Distance patterns of personal networks in four countries: a comparative study - Kowald, Matthias; van den Berg, Pauline; Frei, Andreas; Carrasco, Juan-Antonio; Arentze, Theo; Axhausen, Kay; Mok, Diana; Timmermans, Harry; Wellman, Barry (Journal of transport geography, 2013)
•We compare distances between home locations of personal networks in four countries.•Multilevel models are used to study these distance patterns.•Characteristics of social ties and personal networks are the strongest predictors.•Ego’s socio-demographics are weaker predictors of distance patterns.•Differences between countries exist on ego’s income and ego-alter tie strength. Acknowledging the relevance of social networks on (social) travel behaviour, the objective of this paper is to comparatively study the distance patterns between the home locations of social contacts. Analyses are based on five recent collections of personal network data from four countries: Canada, Switzerland, the Netherlands, and Chile. Multilevel models, which explicitly account for the hierarchical structure of the data sets, are used to study the role of explanatory variables to understand the distance patterns of social contacts. Modelling results suggest that alters’ characteristics (such as type of relationship, emotional closeness, and duration of the relationship) as well as personal network composition (alters with a certain relationship to the ego) constitute stronger predictors than an ego’s socio-demographic information across these countries. In addition, comparative analyses suggest differences between countries on relevant key variables such as an ego’s income and the ego–alter tie strength.